Предмет:
МатематикаАвтор:
анонимУпростим выражение:
(a - 7^2) - 2 * (a - 7) * (a + 7) + (a + 3)^2 = а - 49 - 2 * (а^2 - 7 * а + 7 * а - 49) + а^2 + 3 * а + 3 * а + 9 = - 40 - 2 * а^2 + 28 * а + 98 + а^2 + 7 * а = -а^2 + 35 * а + 58;
Подставим значение а = 1/4:
-(1/4)^2 + 35 * 1/4 + 58 = -1/16 + 35/4 + 58 = -1/16 + 140/16 + 928/16 = (928 + 140 - 1)/16 = 1067/16.
Ответ: 1067/16.
Автор:
harper67Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть